STRATEGI PENCEGAHAN TRAGEDI HAK ASASI PEREMPUAN - Ayub Wahyudin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
The National women's commission released data annually on violence against women that always increase. Policy advocacy effort and socialization on the elimination of violence against women was held across the archipelago. We need a perfect strategy that involves all stakeholders from academic community, community leaders, public officials, law enforcement authorities, the President and all citizens to unite and suppress the liberation of women from violence and discrimination. The tragedy of human rights including women’s rights is an urgent issue to be dealt with.